Platycodin D sensitizes KRAS-mutant colorectal cancer cells to cetuximab by inhibiting the PI3K/Akt signaling pathway - Liu, Yanfei; Tian, Shifeng; Yi, Ben; Feng, Zhiqiang; Chu, Tianhao; Liu, Jun; Zhang, Chunze; Zhang, Shiwu; Wang, Yijia (Frontiers in Oncology, 2022)
Cetuximab is a monoclonal antibody against epidermal growth factor receptor that blocks downstream signaling pathways of receptor tyrosine kinases, including Ras/Raf/MAPK and PI3K/Akt, thereby inhibiting tumor cell proliferation and inducing cancer cell apoptosis. Owing to KRAS mutations, the effectiveness of cetuximab is usually limited by intrinsic drug resistance. Continuous activation of the PI3K/Akt signaling pathway is another reason for cetuximab resistance. Platycodon-D, a bioactive compound isolated from the Chinese herb Platycodon grandiflorum, regulates Akt in different trends based on tissue types. To investigate whether platycodon-D can sensitize KRAS-mutant colorectal cancer cells to cetuximab by inhibiting the PI3K/Akt signaling pathway, HCT116 and LoVo cells were treated with cetuximab and platycodon-D. LY294002 and SC79 were used to regulate Akt to further evaluate whether platycodon-D the sensitizes cells to cetuximab by inhibiting Akt. Our results confirmed that platycodon-D increased the cytotoxic effects of cetuximab, including inhibition of growth, migration, and invasion, via downregulation of PI3K and Akt phosphorylation in HCT116 and LoVo cells both in vitro and in vivo. Given these data, platycodon-D may sensitize KRAS-mutant colorectal cancer cells to cetuximab via inhibition of the PI3K/Akt signaling pathway.